Penerapan Model Personalized Learning untuk Meningkatkan Prestasi Belajar Siswa pada Pembelajaran Matematika - Edi Supraptana; Joko Widiyanto; Ali Murtopo; Muh. Yasid; Suwardi Suwardi; Thoyibah Handayani (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Student achievement plays a vital role in establishing a strong academic foundation and cultivating essential life skills for the future. One instructional model that supports the development of these competencies is personalized learning. A qualitative research approach was employed, involving Mathematics teachers as the primary informants. Data were collected through interviews, observations, and documentation. The findings reveal the following: (1) The implementation of personalized learning involves several key steps: identifying students’ needs and interests, setting individual learning goals, designing flexible instructional strategies, incorporating project-based or contextual learning activities, and providing continuous feedback and reflection opportunities; (2) The benefits of the model include enhanced student engagement, accommodation of diverse learning styles, improved academic performance, the development of independent learning skills, and the creation of an inclusive learning environment; (3) However, several limitations were also identified, including inconsistent implementation, limited assessment frameworks, increased administrative workload for teachers, reliance on technological infrastructure, and variability in student learning outcomes. In conclusion, personalized learning can be effectively implemented in madrasah as a strategic effort to enhance students’ academic achievement and overall learning experience.